Penerapan 4S pada Model Asuhan Keperawatan di Ruang Bedah Wanita dan Ruang Paru BLUD Rumah Sakit Umum Jayapura - Rumbewas, Trisye Yolanda; Wardani, Ratna; Sultan, Sultan (Kolaborasi: Jurnal Pengabdian Masyarakat, 2026)
Introduction: The implementation of standardized nursing care documentation remains a challenge in many hospital units, especially in high-demand wards where workload and time constraints affect nurses’ compliance. The 4S model, comprising SDKI (Nursing Diagnosis Standard), SIKI (Nursing Intervention Standard), SLKI (Nursing Outcomes Standard), and SPO (Standard Operating Procedures), provides a structured approach to ensure consistency, accuracy, and accountability in nursing care. However, limited understanding and practical application among nurses often lead to variations in documentation quality. Objective: This community service aimed to enhance nurses’ understanding and competence in implementing the 4S model through structured training and direct supervision at BLUD Jayapura General Hospital. Method: The program was carried out by nursing lecturers and students from Universitas Strada Indonesia in collaboration with BLUD Jayapura General Hospital. The activities took place from October 10 to 12, 2025, involving 25 participants consisting of 2 head nurses and 23 staff nurses from the Women’s Surgery and Pulmonary Wards. The program included lectures, workshops, group discussions, and on-the-job training. Evaluation was conducted using pre- and post-tests to measure knowledge improvement, and data were analyzed using a paired sample t-test. Result: The average pre-test score was 62.00 ± 8.12, which increased to 86.00 ± 6.47 after the training (p = 0.000). Participants reported better comprehension of the interrelation between SDKI, SIKI, and SLKI, as well as improved ability to formulate nursing diagnoses, interventions, and outcomes. Most participants also expressed that the integrated documentation format simplified their workflow and supported nursing quality audits. Conclusion: The 4S-based nursing care training effectively improved nurses’ knowledge and practical skills in applying standardized nursing documentation. The program strengthened clinical accountability, enhanced documentation consistency, and supported quality improvement initiatives at BLUD Jayapura General Hospital. Future programs are recommended to expand this training model to other hospital units and integrate the 4S framework into electronic nursing documentation systems.